2015
DOI: 10.3390/ijerph120201216
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Pollution from Illegal Waste Disposal and Health Effects: A Review on the “Triangle of Death”

Abstract: The term “triangle of death” was used for the first time by Senior and Mazza in the journal The Lancet Oncology referring to the eastern area of the Campania Region (Southern Italy) which has one of the worst records of illegal waste dumping practices. In the past decades, many studies have focused on the potential of illegal waste disposal to cause adverse effects on human health in this area. The great heterogeneity in the findings, and the bias in media communication has generated great healthcare doubts, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(93 citation statements)
references
References 44 publications
2
85
0
1
Order By: Relevance
“…Acerra is located in "triangle of death", term introduced by Senior and Mazza [22] for the identification of an area delimited by three towns: Nola, Marigliano and Acerra (Figure 1) characterized by the presence of the landfill of hazardous wastes and influenced by illegal waste dumping and burning practices [23]. The composition of landfilled wastes results in different kinds of substances, especially of toxic residues derived from final stages of the industrial processes and therefore containing metals as copper, arsenic, antimony, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Acerra is located in "triangle of death", term introduced by Senior and Mazza [22] for the identification of an area delimited by three towns: Nola, Marigliano and Acerra (Figure 1) characterized by the presence of the landfill of hazardous wastes and influenced by illegal waste dumping and burning practices [23]. The composition of landfilled wastes results in different kinds of substances, especially of toxic residues derived from final stages of the industrial processes and therefore containing metals as copper, arsenic, antimony, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Particular geographical areas are outlined such as "triangle of death" in Campania region (area between Acerra, Nola, and Marigliano municipalities) or the extended area called "Land of Fires" which includes 88 municipalities across Napoli and Caserta provinces [8]. The magnitude of toxic dumping practice is a severe issue for an EU country where statistically all population have access to reliable waste management services.…”
Section: Introductionmentioning
confidence: 99%
“…Metal concentrations in the different groups showed that snails accumulate certain metals (Zn, Pb and Cd) and that this bioaccumulation occurs more in the influence is clearly evident, due not only to the wide extent of local industrial and agricultural activities, but also to the illegal spillage of toxic waste and of uncontrolled fire [30]. These phenomena are in fact the characteristic of the lands between the territory of Caserta and Napoli, which must be therefore the object of intense environmental controls.…”
Section: Discussionmentioning
confidence: 99%